PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Karma Karma (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2020)
Achieving sales targets is not easy, it takes hard work, for example providing friendly service, so consumers feel happy. The logic above is a fact that must be realized, considering that consumers are sensitive. This research was conducted to find out how service efforts have an effect on satisfaction and the impact on repeat purchases. The scientific method uses a quantitative method with 84 respondents. The sample technique uses incidentals, where respondents are asked to provide their responses to the services of a modern retail. To test this, linear regression analysis is used and the findings are found that service contributes to customer satisfaction, especially the attitude of the waiter is very closely related to customer emotions. Furthermore, the empathy indicator gets a good rating, consumers see the friendliness and responsiveness of employees affect the attitude of purchase